2005
DOI: 10.1016/j.ijcard.2004.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Association of two apolipoprotein A-I gene MspI polymorphisms with lipid and blood pressure levels

Abstract: The 83T allele may be associated with a better lipid profile and blood pressure levels in this group of Chinese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
1
20
2
Order By: Relevance
“…Likewise, -75A and ?83T alleles have also been associated with higher HDL levels in some populations [13,14,19,20], whereas this association was not found in others [15,16]. Moreover, ?83T allele was associated with lower triglyceride levels in Chinese population [47]. Our findings did not show any association of -75G/A and ?83C/T polymorphisms with HDL, LDL, VLDL, total cholesterol and triglycerides serum levels in our Brazilian sample.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Likewise, -75A and ?83T alleles have also been associated with higher HDL levels in some populations [13,14,19,20], whereas this association was not found in others [15,16]. Moreover, ?83T allele was associated with lower triglyceride levels in Chinese population [47]. Our findings did not show any association of -75G/A and ?83C/T polymorphisms with HDL, LDL, VLDL, total cholesterol and triglycerides serum levels in our Brazilian sample.…”
Section: Discussioncontrasting
confidence: 75%
“…Moreover, we found an association between ?83C allele and hypertension in the presence of cardiovascular disease. Ma et al [47] did not detect an association between -75G/A polymorphism and hypertension; however, these authors observed that ?83T allele was associated with better profile of HDL levels and blood pressure measure in Chinese population [47]. When the haplotype was analyzed, our data showed that AT haplotype presents significant lower risk to develop hypertension.…”
Section: Discussionmentioning
confidence: 86%
“…These findings are not consistent with those reported by Meng et al (1997), Needham et al (1994), and Ma et al (2005), possibly due to differences in the sample groups between the studies (ethnicity, sex, etc.). We report here that the rs2070665 polymorphism is associated with Lp(α) levels (P < 0.05), which has not been found in other studies.…”
Section: Discussioncontrasting
confidence: 90%
“…Apo A-I is involved in several steps of lipid metabolism, stabilization of lipoprotein structure and the regulation of lipoprotein metabolism (27). Abnormalities in the structure or concentration of Apo A-I can lead to lipid metabolism disorders and induce pathological changes, including hypertension and insulin resistance (28,29).…”
Section: Discussionmentioning
confidence: 99%